Biosorption Potential of Bacillus salmalaya Strain 139SI for Removal of Cr(VI) from Aqueous Solution - Dadrasnia, A.; Wei, K.S.C.; Shahsavari, N.; Sofian-Azirun, Mohd; Ismail, S. (MDPI, 2015)
The present study investigated the biosorption capacity of live and dead cells of a novel Bacillus strain for chromium. The optimum biosorption condition was evaluated in various analytical parameters, including initial concentration of chromium, pH, and contact time. The Langmuir isotherm model showed an enhanced fit to the equilibrium data. Live and dead biomasses followed the monolayer biosorption of the active surface sites. The maximum biosorption capacity was 20.35 mg/g at 25 degrees C, with pH 3 and contact time of 50 min. Strain 139SI was an excellent host to the hexavalent chromium. The biosorption kinetics of chromium in the dead and live cells of Bacillus salmalaya (B. salmalaya) 139SI followed the pseudo second-order mechanism. Scanning electron microscopy and fourier transform infrared indicated significant influence of the dead cells on the biosorption of chromium based on cell morphological changes. Approximately 92% and 70% desorption efficiencies were achieved using dead and live cells, respectively. These findings demonstrated the high sorption capacity of dead biomasses of B. salmalaya 139SI in the biosorption process. Thermodynamic evaluation (G(0), H-0, and S-0) indicated that the mechanism of Cr(VI) adsorption is endothermic; that is, chemisorption. Results indicated that chromium accumulation occurred in the cell wall of B. salmalaya 139SI rather than intracellular accumulation.